Synthetic tambjamine analogues induce mitochondrial swelling and lysosomal dysfunction leading to autophagy blockade and necrotic cell death in lung cancer - Rodilla, Ananda M.; Korrodi-Gregório, Luís; Hernando, Elsa; Manuel-Manresa, Pilar; Quesada, Roberto; Pérez-Tomás, Ricardo; Soto-Cerrato, Vanessa (Biochemical pharmacology, 2017)
[Display omitted] Current pharmacological treatments for lung cancer show very poor clinical outcomes, therefore, the development of novel anticancer agents with innovative mechanisms of action is urgently needed. Cancer cells have a reversed pH gradient compared to normal cells, which favours cancer progression by promoting proliferation, metabolic adaptation and evasion of apoptosis. In this regard, the use of ionophores to modulate intracellular pH appears as a promising new therapeutic strategy. Indeed, there is a growing body of evidence supporting ionophores as novel antitumour drugs. Despite this, little is known about the implications of pH deregulation and homeostasis imbalance triggered by ionophores at the cellular level. In this work, we deeply analyse for the first time the anticancer effects of tambjamine analogues, a group of highly effective anion selective ionophores, at the cellular and molecular levels. First, their effects on cell viability were determined in several lung cancer cell lines and patient-derived cancer stem cells, demonstrating their potent cytotoxic effects. Then, we have characterized the induced lysosomal deacidification, as well as, the massive cytoplasmic vacuolization observed after treatment with these compounds, which is consistent with mitochondrial swelling. Finally, the activation of several proteins involved in stress response, autophagy and apoptosis was also detected, although they were not significantly responsible for the cell death induced. Altogether, these evidences suggest that tambjamine analogues provoke an imbalance in cellular ion homeostasis that triggers mitochondrial dysfunction and lysosomal deacidification leading to a potent cytotoxic effect through necrosis in lung cancer cell lines and cancer stem cells.